Komunikasi Politik dan Diplomasi Berbasis Kearifan Lokal dalam Masa Kampanye Pemilukada Kabupaten Kuantan Singingi Tahun 2011 - Muhammad Ridwan (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2013)
Political communication is important and feels more important when we listen to and browse the functions of political communication itself, especially when political communication and political diplomacy based on local wisdom . Political communication is done to promote the political desires of Regents candidates Singingi Kuantan , poor judgment in taking the values of local wisdom which contains many morals, truth values, family values and religious values can not be blocked causing conflicts terjaddi The Regency Kuantan Singingi Election in 2011. One example of local wisdom kuantan singing the